Efficacy of sunitinib in patients with metastatic or unresectable renal cell carcinoma and renal insufficiency. Issue 4 (March 2015) - Poprach, Alexandr; Bortlicek, Zbynek; Melichar, Bohuslav; Lakomy, Radek; Svoboda, Marek; Kiss, Igor; Zemanova, Milada; Fiala, Ondrej; Kubackova, Katerina; Coufal, Oldrich; Pavlik, Tomas; Dusek, Ladislav; et al.
Abstract: Aim: The aim of this retrospective, registry-based study was to analyse treatment outcomes in patients with metastatic renal cell carcinoma (mRCC) treated with sunitinib and renal insufficiency (RI). Methods: The cohort included 790 patients treated with sunitinib between 2006 and 2013. At the start of sunitinib therapy 22, 234, and 534 patients had severe (glomerular filtration rate [GFR] <30 ml/min/1.73 m 2 ), moderate (GFR 30–60 ml/min/1.73 m 2 ) or mild RI/normal renal function (GFR >60 ml/min/1.73 m 2 ), respectively. Results: For the three groups defined above, median progression-free survival (PFS) (95% confidence interval [CI]) was 5.3 months (0.1–18.5), 8.1 months (6.2–9.9) and 11.3 months (9.4–13.2) ( p  = 0.244), and median overall survival (OS) was 26.3 months (1.2–51.4), 21.2 months (13.2–29.1) and 26.3 months (22.6–29.9) ( p  = 0.443), respectively. The disease control rates were 45.5%, 56.4% and 59.2%, respectively ( p  = 0.374). No unexpected toxicity was reported in the patients with RI, but the treatment was more frequently discontinued because of adverse events and the duration of therapy was significantly shorter in these patients ( p  = 0.007). Conclusions: Duration of first-line targeted treatment for mRCC was significantly shorter for patients with RI, and may have translated into a trend to shorter PFS. These results highlight the need for optimal management of side-effects in patients with mRCC and RI.